2020
DOI: 10.1002/jcla.23212
|View full text |Cite
|
Sign up to set email alerts
|

The influence and impact of smoking on red blood cell morphology and buccal microflora: A case‐control study

Abstract: Background: Tobacco smoking is a major health issue worldwide. In addition to several health problems, smoking can also cause buccal cavity ulcers and buccal cavity cancer in case of chronic smoking. Tobacco smoking may also lead to deranged morphology of red blood cells (RBCs), which results in reduced oxygen carrying capacity of the blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Our study showed a correlation between smoking before pregnancy and reduced levels of MCV, MCH and MCHC (indicating the deformation of erythrocytes), although we found no correlation with the level of hemoglobin (Table 3). These results are in line with the findings of Aldosari et al [54], who report the adverse effect of smoking on erythrocyte shape in pregnant women who either smoked or were exposed to passive smoking. A lack of effect of smoking before pregnancy on hemoglobin levels in our study is interesting in the light of findings reported by Van Tiel et al [55], who showed that an improvement in HgB and HCT in people who quit smoking takes as long as 2 years.…”
Section: Resultssupporting
confidence: 93%
“…Our study showed a correlation between smoking before pregnancy and reduced levels of MCV, MCH and MCHC (indicating the deformation of erythrocytes), although we found no correlation with the level of hemoglobin (Table 3). These results are in line with the findings of Aldosari et al [54], who report the adverse effect of smoking on erythrocyte shape in pregnant women who either smoked or were exposed to passive smoking. A lack of effect of smoking before pregnancy on hemoglobin levels in our study is interesting in the light of findings reported by Van Tiel et al [55], who showed that an improvement in HgB and HCT in people who quit smoking takes as long as 2 years.…”
Section: Resultssupporting
confidence: 93%
“…Age, gender, and lifestyle are demographic factors that affect Hematological parameters. Decreasing value of RBC, Hb, PCV and lymphocytes with aging is observed in men (8). However is another study on Canadians except MCHC, most RBC indices levels tended to increase with age in males (9).…”
Section: Discussionmentioning
confidence: 83%
“…Acute, strenuous exercise provided by a low frequency activity can lead to platelet activation, while regular physical activity can decrease/prevent platelet activation and favorably modulate platelet function ( 130 , 150 , 151 ). This could help to explain the findings of lower PCT and PLT among firefighters who exercise weekly ( Supplementary Table S3 ), corroborating the positive correlations that were found between BMI and PLT (S group), MPV (NS group), and PCT (all firefighters) ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The obtained correlations found for 2-OHFlu (with MON and BAS) and 1-OHPyr (MON, BAS, ALY, and MCV) suggest a possible contribution from cigarette smoke exposure. Smoking is a recognized risk factor for cardiovascular disease development, whose mechanisms are mainly related with inflammation through increased leucocyte count and mutagenic alterations ( 127 , 129 , 151 , 159 , 161 , 162 ). The negative correlations of NEU with 2-OHFlu and EOS with 1-OHPyr only in the NS group suggest that (without tobacco consumption as a variable for increased inflammation) there can be a possible smoking-independent negative impact of the two respective PAHs (fluorene and pyrene) on the first line of immune defense (NEU) and allergenic pathways (EOS).…”
Section: Discussionmentioning
confidence: 99%